The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1128/spectrum.01346-22
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Molecular Characteristics of mcr-9 in Citrobacter spp. from Healthy Individuals and Patients in China

Abstract: The emergence of mcr homologues posed a serious threat to the therapeutic efficiency of polymyxin antibiotics. Citrobacter freundii is generally regarded as an opportunistic pathogen associated with a variety of nosocomial infections. In this study, we investigated the prevalence of mcr-9 in Citrobacter spp. isolates from healthy individuals and infected patients and highlighted the importance of the rational use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
0
0
Order By: Relevance
“…WF0003 carries mcr-9 genes, but it is susceptible to colistin. This is consistent with Ju’s study, which isolated nine strains of Citrobacter carrying mcr-9 , all of which were sensitive to colistin [ 49 ]. Kieffer’s study showed that the expression of mcr-9 could be induced by subinhibitory concentrations of colistin in the presence of qseB and qseC .…”
Section: Discussionsupporting
confidence: 92%
“…WF0003 carries mcr-9 genes, but it is susceptible to colistin. This is consistent with Ju’s study, which isolated nine strains of Citrobacter carrying mcr-9 , all of which were sensitive to colistin [ 49 ]. Kieffer’s study showed that the expression of mcr-9 could be induced by subinhibitory concentrations of colistin in the presence of qseB and qseC .…”
Section: Discussionsupporting
confidence: 92%
“…Studies on carbapenemresistant Citrobacter spp. found that the Inc family of plasmids was the primary group that carries genes for carbapenem resistance (Cao et al, 2021;Dziri et al, 2022;Ju et al, 2022); and was one of the main reasons for the rapid dissemination of carbapenem-resistant Citrobacter spp. around the world.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…of Citrobacter, including mcr-1 in C. freundii (Li et al, 2017;Yan Hu et al, 2017) and mcr-1 in C. braakii (Sennati et al, 2017;Liu et al, 2018a), and mcr-1.5 in C. amalonaticus (Faccone et al, 2019), mcr-3.5 in C. sedlakii and C. amalonaticus (Phuadraksa et al, 2023), mcr-9 (Bitar et al, 2020) in C. freundii and, chromosomal mcr-9 in C. telavivensis (Ribeiro et al, 2021). In Citrobacter spp., mcr can cooccur with genes conferring resistance to b-lactams (Faccone et al, 2019) and aminoglycosides (Ju et al, 2022). This may result in developing MDR strains that are challenging to manage using currently available antibiotics.…”
Section: Antibiotic Resistancementioning
confidence: 99%